Technologies to embrace the sun: solarpunk-based project as an exploration for a just energy transition - Juan David Reina-Rozo; Azucena Castro; Francisco Zambrano-Caviedes; Agustín Neko Epieyu (Revista Iberoamericana de Estudios de Desarrollo)
The national implementation of electricity generation projects directly threatens the livelihoods of local and Indigenous communities in Latin America. Therefore, it is crucial to search for solutions to energy supply considering local needs and cosmologies. This article focuses on micro-energy production in rural settlements on the Colombian Caribbean coast. The aim is to provide insights into the relationship between energy, technology, and ancestrality through the lens of solarpunk storytelling. To explore this theme, we present the «tech to embrace the sun» initiative as a case study to co-design and imagine desirable futures by the local community of Selvatorium, in La Guajira. The results consist of the development of seven future ancestral stories co-written by community members and guests, two guides to build two prototypes, and a fanzine. The project concludes with empirical and theoretical insights for development studies about sustainable energy futures.